2014
DOI: 10.1111/cdev.12313
|View full text |Cite
|
Sign up to set email alerts
|

The Cascading Development of Autonomy and Relatedness From Adolescence to Adulthood

Abstract: We tested a developmental cascade model of autonomy and relatedness in the progression from parent to friend to romantic relationships across ages 13, 18, and 21. Participants included 184 adolescents (53% female, 58% Caucasian, 29% African American) recruited from a public middle school in Virginia. Parental psychological control at age 13 undermined the development of autonomy and relatedness, predicting relative decreases in autonomy and relatedness with friends between ages 13 and 18 and lower levels of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 71 publications
9
93
0
1
Order By: Relevance
“…This idea is mirrored by attachment theory (Bowlby, 1973), which emphasizes that the balance of autonomy and relatedness is important for close relationships. Specifically, scholars suggest that adolescents who fail to strike a balance between autonomy and relatedness are more likely to utilize hostile tactics in relationship interactions as a way to maintain control (Oudekerk, Allen, Hessel, & Molloy, 2015). From an attachment perspective, parental intrusiveness damages adolescents working models of themselves and relationships, because it inhibits adolescents' confidence in navigating social interactions (Bowlby, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is mirrored by attachment theory (Bowlby, 1973), which emphasizes that the balance of autonomy and relatedness is important for close relationships. Specifically, scholars suggest that adolescents who fail to strike a balance between autonomy and relatedness are more likely to utilize hostile tactics in relationship interactions as a way to maintain control (Oudekerk, Allen, Hessel, & Molloy, 2015). From an attachment perspective, parental intrusiveness damages adolescents working models of themselves and relationships, because it inhibits adolescents' confidence in navigating social interactions (Bowlby, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents reconsider the boundaries that divide which issues are subject to parents' authority versus adolescents' personal jurisdictions (Laursen & Collins, 2009). This occurs at a time when parents are experiencing increases in parenting stress (Putnick et al, 2010) and must adjust their parenting in order to balance individuality and togetherness in the parent-adolescent relationship to accommodate adolescents' increasing needs for autonomy (Oudekerk et al, 2015). For example, adolescents and parents tend to agree that parents should set limits for adolescent safety, social conduct, and morality issues.…”
Section: Introductionmentioning
confidence: 99%
“…These findings build on previous research that has demonstrated an association between parent–adolescent relationships and adolescents’ neurobiological response to stress (Byrd-Craven et al 2012; Spies et al 2011). Most importantly, our study is the first study to exclusively focus on autonomy and relatedness, a distinct construct from other parenting behaviors, that is critical for adolescents to become self-regulating autonomous adults and has been associated with lifelong positive development (Oudekerk et al 2015). The findings also suggest that adolescents whose mothers undermine autonomy and relatedness and who report higher perceived stress evidence a heightened HPA-axis and cardiovascular response.…”
Section: Resultsmentioning
confidence: 99%
“…As adolescents transition into a new developmental stage, they encounter developmental tasks (e.g., developing autonomy, identity development) that are important to successfully negotiate to adjust to new demands or take advantage of new opportunities within the current developmental stage, as well as subsequent stages (Erikson 1968; Oudekerk et al 2015). Failure to resolve a developmental task can put youth at risk for solving other important tasks and impact outcomes in a variety of areas (Masten and Cicchetti 2010).…”
Section: Autonomy Relatedness and Stress Responsementioning
confidence: 99%
“…The long path to homicide begins at home and in the genes, with many thousands of research articles suggesting a plethora of causes. For example, just recently, Ouderek et al (2014) followed a cohort of children 13, 18, and 21 and found those with strict and controlling parents tend to produce awkward children who are loathe to express their opinions and are not good at resolving conflict with peers even into adult life. Thus, active students as well as nonstudents often view the school as a symbol of what hurt them.…”
Section: Introductionmentioning
confidence: 99%